Valorizing intangible cultural heritage through community-based tourism in Lăpuș Land, Transylvania - Nechita, Florin; Candrea, Adina Nicoleta; Csiszér, Annamaria; Tanaka, Hiromasa (My University, 2018)
Community-based tourism has been promoted as a means of development whereby the social, environmental and economic needs of local communities are met through the offering of a tourism product. Local culture may be a community’s most valuable asset for tourism if planned and managed properly. Its intangible cultural heritage may provide a community with a competitive advantage and uniqueness, one that differentiates it from all other communities. However, with increasing commodification of tourism, many smaller rural communities face several challenges in developing community-based tourism. The present paper explores the concept of community-based tourism, as a basis for the valorization of intangible cultural heritage, with a special focus on a regional tourist destination in Romania. Aiming to identify tourists’ experience, a research was conducted among Japanese visitors who discovered the intangible cultural heritage of the studied area during an academic summer camp.
Keywords: community-based tourism; intangible heritage; rural destinations; traditions